Estudos sociais da infância: discutindo a constituição de um campo a luz de Bourdieu (Childhood social studies: discussing the constitution of a feld in the light of Bourdieu) - Prado, Renata Lopes Costa; Voltarelli, Monique Aparecida (Revista Eletrônica de Educação, 2018)
Abstract This article seeks to draw upon Pierre Bourdieu’s theory of the scientific feld in order to better understand the emergence of childhood social studies. This feld views children as actors with signifcant participation in the construction of history and culture, and childhood as a social construction and also as a structural category subordinate in society. By means of a theoretical essay, the ruptures and paradigmatic changes relating to three important felds – anthropology, psychology and sociology, all of which encompass the study of children and the childhood – will be emphasized. The panoramic presentation of dominant trends in these areas and aspects that were the subject to criticism from researchers of childhood social studies will allow differences between traditional paradigms and emerging ones to be illuminated, whilst also allowing for common and shared influences between one feld and another to be observed. It is argued here that reflecting on a scientifc object is breaking away from common sense (established by speeches over time) and socially accepted scientific representations. The article concludes by proposing that the theory of scientific felds provides a productive feld for analyzing the development of childhood social studies. In this regard, other studies which aim to follow up on the discussions presented here are suggested. Keywords: Childhood social studies, Scientific field, Paradigms. Resumo O presente artigo se propõe a dialogar com as contribuições da teoria de Pierre Bourdieu sobre o campo científico a fim de melhor compreender a emergência dos estudos sociais da infância, um campo que partilha entre si a visão das crianças como atores com signifcativa participação na construção da história e da cultura, a visão da infância como construção social e, também, como categoria estrutural subordinada da sociedade. Para essa discussão, em forma de ensaio teórico, enfatizam-se rupturas e mudanças paradigmáticas a partir de três importantes campos que, entre outros assuntos, dedicam-se ao estudo das crianças e da infância: a antropologia, a psicologia e a sociologia. A apresentação panorâmica de correntes dominantes nessas áreas e de aspectos que foram objetos de críticas dos pesquisadores dos estudos sociais da infância permite iluminar diferenças entre paradigmas tradicionais e emergentes, além de possibilitar a observação de influências mútuas entre um campo e outro. Argumenta-se aqui que refletir sobre um objeto científco é romper com um sentido comum (instaurado por discursos ao longo do tempo) e com representações científicas socialmente aceitas. Conclui-se que a teoria dos campos científicos se constitui como terreno fértil para análises sobre o desenvolvimento dos estudos sociais da infância. Nesse sentido, outras pesquisas que deem continuidade às discussões ora apresentadas são sugeridas. Palavras-chave: Estudos sociais da infância, Campo científico, Paradigmas. Resumen Este artículo pretende dialogar con las contribuciones de la teoría del campo científico de Pierre Bourdieu para comprender mejor los estudios sociales de la infancia, un campo que comparte la visión de los niños como actores con una importante participación en la construcción de la historia y la cultura, la visión de la niñez como una construcción social y también, como una categoría estructural subordinada de la sociedad. Para esta discusión, en forma de ensayo teórico, se hace hincapié en las rupturas y cambios paradigmáticos desde tres importantes campos que, entre otras cosas, se dedican al estudio de los niños y la infancia: la antropología, la psicología y la sociología. La presentación panorámica de las corrientes dominantes en estas áreas y los aspectos que han sido objeto de críticas por los investigadores de los estudios sociales de los niños, permite iluminar tanto las diferencias entre los paradigmas tradicionales y emergentes, como observar las influencias mutuas entre un campo y otro. Aquí se argumenta que reflexionar sobre un objeto científco es romper con el sentido común (establecido por discursos a lo largo del tiempo) y las representaciones científicas socialmente aceptadas. Se concluye que la teoría del campo científico constituye un terreno fértil para el análisis sobre el desarrollo de los estudios sociales de la infancia. En este sentido, se sugieren otros estudios para el seguimiento de las discusiones que aquí se presentan. Palabras clave: Estudios sociales de la infancia, Campo científco, Paradigmas. References ABRAMOWICZ, A. A pesquisa com crianças e infâncias e a sociologia da infância. In: FARIA, A. L. G.; FINCO, D. Sociologia da infância no Brasil. Campinas: Autores Associados, 2011. p. 17-36. ALANEN, L. Repensando a infância, com Bourdieu. Revista NUPEM, v. 6, n. 11, p. 39-55, jul./dez. 2014. ALANEN, L. Teoria do bem-estar das crianças. Cadernos de Pesquisa, v. 40, n. 141, p. 751-775, set./dez. 2010. BOURDIEU, P. O campo científico. In: ORTIZ, R. (Org.). Pierre Bourdieu: Sociologia. São Paulo: Ática, 1983. p. 122-155. BOURDIEU, P. Las reglas del arte. Génisis y estructura del campo literario. Barcelona: Anagrama, 1997. BOURDIEU, P. O poder simbólico. RJ: Bertrand Brasil, 2000. BOURDIEU, P. Razões Práticas: sobre a teoria da acção. Oeiras: Celta Editora, 2002. BOURDIEU, P. Coisas ditas. São Paulo: Brasiliense, 2004a. BOURDIEU, P. Os usos sociais da ciência: por uma sociologia clínica do campo científico. SP: UNESP, 2004b. BOURDIEU, P. Homo academicus. Florianópolis: Ed. da UFSC, 2013. BOURDIEU, P.; WACQUANT, L. Respuestas por una antropología reflexiva. México: Grijalbo, 1995. BURMAN, E. Deconstructing development psychology. Londres: Routledge, 1999. CASTRO, L. R. The ‘good-enough society’, the ‘good-enough citizen’ and the ‘good-enough student’: Where is children’s participation agenda moving to in Brazil? Childhood,v. 19, p. 1-7, 2011. CHRISTENSEN, P.; PROUT, A. Antropological and sociological perspectives on study of children. In: GREENE, S.; HOGAN, D. (Org.). Researching children’s experience. London: Sage, 2005. COHN, C. Antropologia da criança. Rio de Janeiro: Jorge Zahar Ed., 2005. CORSARO, W. A. Sociologia da Infância. Porto Alegre: Artmed, 2011. GAITÁN MUÑOZ, L. La nuevasociología de la infancia. Aportaciones de una mirada distinta. Política y Sociedad, v. 43, n. 1, p. 9-26, 2006. HIRSCHFELD, L. A. Why don’t anthropologists like children? American Anthropologist, v. 104, n. 2, p. 611-627, 2002. HOGAN, D. Researching ‘the child’ in developmental psychology. In: GREENE, S.; HOGAN, D. (Org.). Researching children’s experience: methods and approaches.Londres: Sage Publications, 2006. JAMES, A.Giving voice to children’s voices: practices and problems, pitfalls and potentials. American Anthropologist, v. 109, n. 2, p. 261-272, 2007. JAMES, A.; PROUT, A. Introduction. In: ______ (Org.). Constructing and reconstructing childhood: contemporary issues in the Sociological study of childhood. New York: RoutledgeFalmer, 1997. p. 1-9. JAMES, A.; JAMES, A. Key concepts in childhood studies.Londres: Sage, 2008. JENKS, C. Constituindo a criança. Educação, Sociedade & Cultura, n. 17, p. 185-216, 2002. LEE, N. Vozes das crianças, tomada de decisão e mudança. In: MÜLLER, F. (Org.). Infância em perspectiva: políticas, pesquisas e instituições. São Paulo: Cortez, 2010. p. 42-64. MARCHI, R. As teorias da socialização e o novo paradigma para os estudos da infância. Educação & Realidade, v. 34, n. 1, p. 227-246, jan./abr. 2009. MOLLO-BOUVIER, S. Transformações dos modos de socialização das crianças: uma abordagem sociológica. Educação&Sociedade, v. 26, n. 91, p. 391-403, maio/ago. 2005. MONTGOMERY, H.An introduction to childhood: anthropological perspectives on children’s lives. West Sussex (UK): Wiley-Blackwell, 2009. PIAGET, J. O nascimento da inteligência na criança. Rio de Janeiro: Zahar, 1970. PRADO, R. L. C. William Corsaro: outro olhar entre os pares (entrevista). Revista Carta Fundamental, p. 52-55, jun. 2011. PROUT, A. Participação, políticas e as condições da infância em mudança. In: MÜLLER, Fernanda (Org.). Infância em perspectiva: políticas, pesquisas e instituições. São Paulo: Cortez, 2010a. p. 21-41. PROUT, A. Reconsiderando a nova sociologia da infância. Cadernos de Pesquisa, v. 40, n. 141, p. 729-750, set./dez. 2010b. QVORTRUP, J. Childhood and societal macrostructures. In: GULDBERG, J.; MOURITSEN, F.; MARKER, T. (Org.). Working paper 9. Odense: Odense University, 1999. p. 3-22. QVORTRUP, J. A tentação da diversidade – e seus riscos. Educação e Sociedade, Campinas, v. 31, n. 113, p. 1121-1136, out./dez., 2010a. QVORTRUP, J. A infância enquanto categoria estrutural. Educação e Pesquisa, São Paulo, v. 36, n. 2, p. 631-643, 2010b. QVORTRUP, J.; CORSARO, W.; HONIG, M. S. Why social studies of childhood? An introduction to the handbook. In: QVORTRUP, J.; CORSARO, W.; HONIG, M. S. (Org.). The Palgrave handbook of childhood studies. Hampshire (UK): Palgrave Macmillan, 2009. p. 1-17. ROSEMBERG, F. Educação como uma forma de colonialismo. Revista Ciência e Cultura, n. 28, v. 12, p. 1466-1471, 1976. SARMENTO, M. J. Sociologia da Infância: correntes e confluências. In: SARMENTO, M. J.; GOUVEA, M. C. S. Estudos da Infância: educação e práticas sociais. Petrópolis, RJ: Vozes, 2008. p. 17-39. SARMENTO, M. J.; MARCHI, R. C. Radicalização da infância na segunda modernidade: para uma sociologia da infância crítica. Configurações, Braga, n. 4, p. 91-113, 2008. SIROTA, R. Emergência de uma sociologia da infância: evolução do objeto e do olhar. In: Cadernos de Pesquisas, n. 112, p. 7-31, mar. 2001. TEBET, G. G. C.; ABRAMOWICZ, A. O bebê interroga a sociologia da infância. Linhas Críticas, v. 20, n. 41, p. 43-61, jan./abr. 2014. WOODHEAD, M.; FAULKNER, D. Sujeitos, objectos ou participantes?In: CHRISTENSEN, P.; JAMES, A. (Org.). Investigação com crianças: perspectivas e práticas. Porto: Escola Superior de Educação de Paula Frassinetti, 2005. p. 1-28.